Beauty Crush Cosmetics / Nashiha Shakinah Rajuli - Rajuli, Nashiha Shakinah (2018)
The name of my business is Beauty Crush Cosmetics. My product Beauty Crush lip matte. This product is available in five (5) code colors which is Rose, Truelove, Blush, Fuchsia and Cherry. All these colors are natural and bright.